1990
DOI: 10.1093/oxfordjournals.eurheartj.a059710
|View full text |Cite
|
Sign up to set email alerts
|

Errors in measurements of stroke volume for invasive and echo-Doppler evaluations of valvular regurgitant fractions. Clinical evaluation and computer simulation Intra-arterial blood pressure monitoring in the evaluation of the hypertensive athlete

Abstract: The aim of this study was to compare cardiac catheterization (CATH) with 2D echo-Doppler (ED) in clinically evaluating the stroke volumes (SV) needed to calculate aortic and mitral regurgitant fractions (aortic and mitral SV for the ED method, thermodilution and angiographic SV for the CATH). As there is no 'gold standard' for this kind of measurement, only subjects without valvular regurgitation were considered. In these subjects, though the two SV measurements needed to calculate the regurgitant volume shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Conversely, PISA overestimates regurgitation due to mitral valve prolapse and nonoptimal flow convergence . The volumetric Doppler method for MR suffers from geometrical assumptions, measurement variability, and requisite lack of important aortic insufficiency …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, PISA overestimates regurgitation due to mitral valve prolapse and nonoptimal flow convergence . The volumetric Doppler method for MR suffers from geometrical assumptions, measurement variability, and requisite lack of important aortic insufficiency …”
Section: Introductionmentioning
confidence: 99%
“…3 The volumetric Doppler method for MR suffers from geometrical assumptions, measurement variability, and requisite lack of important aortic insufficiency. 4 2D PISA quantitation affects clinical outcome for MR, 5,6 tricuspid regurgitation (TR), 7 aortic regurgitation (AR), 8,9 and prosthetic perivalvular regurgitation. 10 Limitations of the 2D PISA method include assessment in a single anatomic plane, nonhemispheric isovelocity shells, asymmetric or eccentric flow convergence, suboptimal convergence and interrogation window, 8 and changes in PISA radius throughout systole 11,12 for MR, and presence of multiple regurgitant jets.…”
Section: Introductionmentioning
confidence: 99%
“…In a beat to beat simultaneous echoventriculographic study done by graphic and angiographic methods had significant systematic errors in calculating the stroke volume, such that the trans-mitral echocardiographic stroke volume tended to be larger than the aortic and the angiographic stroke volume tended to be larger than that obtained by the thermodilution m e t h~d .~ Random errors on the basis of catheterization and echocardiographic measurements are attnibuted to the thermodilution technique by 4%, to angiography by 1 O%, to the measurement of the aortic annulus by 6% and to the aortic velocity time integral by 8%. 4 It is reported that the difference between total left ventricular stroke volume from biplane angiograms and forward stroke volume by the Fick method is often off by 20%.334 Although we have shown a consistent underestimation of left ventricular volumes and the regurgitant fraction by echocardiography when compared to cardiac catheterization, we feel that careful methodology should allow a reliable measurement for the serial evaluation and management of the individual patient.…”
Section: Discussionmentioning
confidence: 68%